Polyampholyte polymer as a stabiliser for subgrade soil. Issue Volume 19:Issued 6(2018) (3rd June 2018) - Rodriguez, Ana K.; Ayyavu, Chandramohan; Iyengar, Srinath R.; Bazzi, Hassan S.; Masad, Eyad; Little, Dallas; Hanley, Howard J. M.
Abstract: This study evaluates the potential of selected ionic polymers to act as pavement subgrade binders. Investigations were based on their relative performance with a Qatari soil which was selected as typical of a pavement subgrade to be found in the Middle East and North African region. The polymeric binders chosen were three synthetic ionic variations of polyacrylamide: cationic poly(acrylamidopropyl trimethyl ammonium chloride) (designated PAMTAC), anionic hydrolysed poly(acrylamide) (HPAM) and the ampholitic terpolymer poly(acrylamide-co-sodiumacrylate-co-(3-acrylamidopropyl) trimethylammonium chloride) (TPAM). The polymers were characterised by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic spectroscopy ( 1 H-NMR and 13 C-NMR). The comparative performance of the polymer-treated soil was judged on the basis of results obtained from selected standard mechanical test data: specifically, the unconfined compressed strength, the stiffness modulus and the toughness. It is concluded that a 50% w/w aqueous solution of the ampholitic terpolymer applied at a dosage of 2.0% by dry weight of the soil gives the best subgrade stabilisation. Of some significance, it is further noted that this ampholitic polymer was superior as a binding agent to the traditional standard, Portland cement, judged under equivalent but nonstandard conditions. Modifying the polymer to act as a binder for subgrade soils in general is also discussed.